The dual-polarization radar signature of a wind turbine: characterization and suppression - Beauchamp, Robert M., author; Chandrasekar, V., advisor; Cheney, Margaret, committee member; Jayasumana, Anura P., committee member; Mielke, Paul, committee member (Colorado State University. Libraries, 2016)
Wind turbines can represent large, dynamic targets for radar systems. Their echoes can inhibit normal radar operations for observation volumes in and beyond the ranges occupied by the turbines. As a result of this interference, also referred to as "wind turbine clutter," the construction and location of wind turbines is restricted, and radar operations are limited to suboptimal performance in the contaminated areas. With the exponential growth of wind energy production, reducing the interference caused by wind turbines is critical to maintaining the performance of radar systems. In this work, characterizations of precipitation, ground clutter, and wind turbines are presented using dual-polarization weather radar observations. Without direct knowledge of a wind turbine's operating state, the physical characteristics of the turbine---specifically, its cyclostationarity---are exploited to implement a temporal suppression method to mitigate wind turbine clutter. Using the cyclostationary characteristics, 15-20 dB of suppression of the turbine blades' signature is demonstrated. A field experiment that simultaneously collected radar observations of a wind turbine and turbine state telemetry is also discussed in this work. Characteristics of the wind turbine's signature are evaluated according to the turbine's state. With this, it is demonstrated that the radar signature of the turbine is deterministic for a given turbine's state and can be modeled. With the observation-based model and state telemetry, the wind turbine blades' signature can be significantly suppressed (by more than 25 dB) in radar observations.
Keywords: clutter suppression; radar; wind turbine; filtering; characterization; signal processing